Pheochromocytoma presenting with recurrent syncope, prolonged QT interval and macroscopic T-wave alternans - Raghav Bansal; Bhavik Dhirawani; Chetan Rathi; Yash Lokhandwala (Annals of Pediatric Cardiology)
An 11-year-old boy presented with recurrent exertional syncope for 1 month. The baseline electrocardiogram (ECG) suggested a diagnosis of long QT syndrome with macroscopic T-wave alternans. Volatility of blood pressure and left ventricular hypertrophy triggered further investigations, revealing pheochromocytoma as the primary cause. The child underwent laparoscopic resection of the tumor with subsequent resolution of ECG changes and symptoms. The genetic testing was negative for known mutations implicated with prolonged QT interval.